2021
DOI: 10.1038/s41598-021-85589-5
|View full text |Cite
|
Sign up to set email alerts
|

Death agonist antibody against TRAILR2/DR5/TNFRSF10B enhances birinapant anti-tumor activity in HPV-positive head and neck squamous cell carcinomas

Abstract: Head and neck squamous cell carcinomas (HNSCC) induced by human papillomavirus (HPV) have increased recently in the US. However, the distinct alterations of molecules involved in the death pathways and drug effects targeting inhibitor of apoptosis proteins (IAPs) have not been extensively characterized in HPV(+) HNSCC cells. In this study, we observed the distinct genomic and expression alterations of nine genes involved in cell death in 55% HNSCC tissues, which were associated with HPV status, tumor staging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In some cell lines, SMAC mimetics by themselves induced cell death in the form of apoptosis or necroptosis 19,20 . However, in most cases, IAPi sensitized the cell lines to extrinsic TNF‐α or TNF‐related apoptosis‐inducing ligand (TRAIL), often with synergistic activity when both TNF/TRAIL and a SMAC mimetic were added 15,19–26 . Several studies by multiple independent research groups have shown synergistic activity of SMAC mimetics when combined with radiation in mice inoculated with xenografts of human HNSCC cell lines, including HPV‐positive/negative models and four different IAPi (birinapant, xevinapant, tolinapant, and LCL161).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cell lines, SMAC mimetics by themselves induced cell death in the form of apoptosis or necroptosis 19,20 . However, in most cases, IAPi sensitized the cell lines to extrinsic TNF‐α or TNF‐related apoptosis‐inducing ligand (TRAIL), often with synergistic activity when both TNF/TRAIL and a SMAC mimetic were added 15,19–26 . Several studies by multiple independent research groups have shown synergistic activity of SMAC mimetics when combined with radiation in mice inoculated with xenografts of human HNSCC cell lines, including HPV‐positive/negative models and four different IAPi (birinapant, xevinapant, tolinapant, and LCL161).…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 However, in most cases, IAPi sensitized the cell lines to extrinsic TNF‐α or TNF‐related apoptosis‐inducing ligand (TRAIL), often with synergistic activity when both TNF/TRAIL and a SMAC mimetic were added. 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Several studies by multiple independent research groups have shown synergistic activity of SMAC mimetics when combined with radiation in mice inoculated with xenografts of human HNSCC cell lines, including HPV‐positive/negative models and four different IAPi (birinapant, xevinapant, tolinapant, and LCL161). The anti‐tumor activity of these combinations was remarkable in these aggressive xenograft models, resulting in the cure of most tumor‐bearing mice.…”
Section: Introductionmentioning
confidence: 99%